Understanding the concept of integrity among staff of Malaysian Immigration Department - Anuar Puteh,; Khazri Osman,; Abdul Ghafar Don,; Nor Akrimi Mohd Ali, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Integrity is absolutely necessary to produce a noble society that is professionally advanced. This study is based on issues and problems of integrity that are often associated with civil servants in Malaysia. Therefore, the aim of the study is to examine the understanding of Immigration Department staff on the integrity concept. This quantitative study applies survey method. The researcher used simple random sampling to select 170 respondents from a total of 190 people in the workforce. However, the total sample obtained in this study was only 157 because some questionnaires were not returned, so they had to be canceled so as not to negatively affect the accuracy of the results. The study finds that the understanding level of Kelantan Immigration Department staff on the integrity concept records a mean score of (m = 4.20, sd = .413). The finding reveals that immigration officers have high level of understanding regarding the integrity concept. Based on the result of the study, various efforts should be undertaken by all parties including the society, educational institutions, religious institutions, and the government to ensure that personal values and values in employment continue to be instilled among civil servants in Malaysia to achieve a high level of integrity.